Acute Coronary Syndrome in Dextrocardia : A Case Report - Ni Kadek Nadia Ayu Agustini; Komang Aditya Yudistira (Aesculapius Medical Journal, 2025)
Dextrocardia is a rare congenital condition in which the heart is positioned on the right side of the thorax, with an estimated incidence of one in 10,000 individuals. Recognizing acute coronary syndrome (ACS) in patients with dextrocardia and situs inversus is challenging due to the anatomical reversal of internal organs. We report a case of a 67-year-old woman presenting with substernal chest pain radiating to the back for 12 hours, accompanied by shortness of breath. The patient had no history of hypertension or diabetes mellitus. Physical examination revealed elevated blood pressure, while other findings were unremarkable. The electrocardiogram (ECG) demonstrated marked right axis deviation with T-wave inversion in leads V1–V4. Chest radiography showed an inverted cardiac silhouette and a right-sided gastric air bubble. In patients without a known diagnosis of dextrocardia, the recognition of ACS can be challenging because clinical and ECG findings may appear reversed. In patients with confirmed or suspected dextrocardia, performing a right-sided ECG and reversed limb lead are essential to accurately identify ischemic changes and avoid misdiagnosis of acute coronary syndrome.